Penanaman nilai nasionalisme melalui kurikulum mata kuliah Pendidikan Kewarganegaraan pada mahasiswa STIKES Surabaya - Muhammad Shofiyul Umam; Diah Mita Widiani; Priska Arlinda Permata Putri (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
Purpose of this study is to determine and describe whether the students have implanted Citizenship Education in the values of nationalism in the Surabaya College of Health Sciences. The research method used is a qualitative method (research and problem) which consists of several questions, namely: 1. Student interest in civics courses, 2. Assessment of whether students have applied the value of nationalism to the Surabaya College of Health Sciences. 3. Knowledge whether or not students understand the meaning of nationalism. This research is aimed at several students of the Surabaya College of Health Sciences in semester 1, semester 3, and semester 5. The results obtained are only 38% of students who have applied and instilled the values of nationalism in the Surabaya College of Health Sciences.